2
$\begingroup$

How to calculate the determinant of this matrix $A=\begin{bmatrix} \sin x & \cos^2x & 1 \\ \sin x & \cos x & 0 \\ \sin x & 1 & 1 \end{bmatrix}$

$$\left[A\right]=\begin{vmatrix} \sin x & \cos^2x & 1 \\ \sin x & \cos x & 0 \\ \sin x & 1 & 1 \end{vmatrix}=\\=\sin x\begin{vmatrix} \cos x& 0\\ 1 & 1 \end{vmatrix}-\cos^2x\begin{vmatrix} \sin x & 0 \\ \sin x & 1 \end{vmatrix}+\begin{vmatrix} \sin x & \cos x\\ \sin x & 1\\\end{vmatrix}=\\=\sin x\cos x-\cos^2x\sin x+\sin x-\sin x\cos x =\\=\sin x\left(\cos x-\cos^2x+1-\cos x\right)=\sin x \left(1-\cos ^2x\right)=\\=\sin x\cdot \sin^2x=\sin^3x$$

The path is something like this? I'm using the wrong rule?

$\endgroup$
  • 3
    $\begingroup$ it is ok: you got the right sign in the middle $\endgroup$ – Avitus Dec 11 '13 at 13:14
  • 3
    $\begingroup$ Everything looks fine to me. $\endgroup$ – Salech Rubenstein Dec 11 '13 at 13:15
  • 1
    $\begingroup$ That is correct. There are probably some simplifications are trig properties you can apply. $\endgroup$ – apnorton Dec 11 '13 at 13:18
  • 1
    $\begingroup$ You could also expand using the last column because it contains one zero. This way you have to calculate one less $2 \times 2$ determinants but yeah :) $\endgroup$ – Slugger Dec 11 '13 at 13:18
4
$\begingroup$

The calculation will be easier if you showed zeros:

Subtract the first row from the second and third row and develop relative the first column we find $$\det A=\begin{vmatrix} \sin x & \cos^2x & 1 \\ \sin x & \cos x & 0 \\ \sin x & 1 & 1 \end{vmatrix}=\begin{vmatrix} \sin x & \cos^2x & 1 \\ 0& \cos x(1-\cos x) & -1 \\ 0& 1-\cos^2x & 0 \end{vmatrix}=\sin x(1-\cos^2x).$$

$\endgroup$
  • $\begingroup$ Indeed, much easier this way! +1 $\endgroup$ – Namaste Dec 11 '13 at 13:28
  • $\begingroup$ I like ... (+1) $\endgroup$ – marcelolpjunior Dec 11 '13 at 13:29
1
$\begingroup$

$$\left[A\right]=\begin{vmatrix} \sin x & \cos^2x & 1\\ \sin x & \cos x & 0 \\ \sin x & 1 & 1 \end{vmatrix}\begin{vmatrix} \sin x & \cos^2x \\ \sin x & \cos x \\ \sin x & 1 \end{vmatrix}=\sin x\cos x+\sin x-\sin x\cos x -\sin x\cos^2x=\\=\sin x\left(1-\cos^2 x\right)=\\=\sin x\cdot \sin^2x=\sin^3 x$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.